Experience sociology - Croteau, David; Hoynes, William (New York, NY McGraw-Hill Education, 2018)
"Experience Sociology has set the new standard for teaching Introductory Sociology. Approaching sociology through the key concepts of culture, structure, and power, the program enables students to see sociology everywhere, and make the familiar new. Presented in an accessible and engaging way that brings theory and sociological concepts together, students move beyond their individual perspective to gain a true sociological perspective. Connect, the proven online experience, adapts to the student's learning needs, enhancing the understanding of topics and developing their sociological imagination."
Machine generated contents note: Part 1: The Sociological Perspective 1: Sociology in a Changing World 2: Understanding the Research Process -- Part 2: Sociology's Core Concepts: Tools for Analysis and Understanding 3: Culture 4: Social Structure 5: Power -- Part 3: The Social Self 6: Socialization 7: Interaction, Groups, and Organizations 8: Deviance and Social Control -- Part 4: Identity and Inequality 9: Class and Global Inequality 10: Race and Ethnicity 11: Gender and Sexuality -- Part 5: Social Institutions and Social Issues 12: Family and Religion 13: Education and Work 14: Media and Consumption 15: Communities, the Environment, and Health 16: Politics and the Economy 17: Social Change: Globalization, Population and Social Movements.
Includes bibliographical references (pages 476-508) and indexes.
Keywords: Sociology